Revitalisasi Ritual Pakon melalui Program Edukasi dan Dokumentasi Budaya Berbasis Masyarakat - Mohamad Yudisa Putrajip; Daffa Satya Jaya Buana; Lalu Yayan Ardiansyah; Azril Irzam; Dedy Sofian Mz (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2026)
: The Pakon ritual, part of the Sasak community tradition in Lombok, holds strong social, spiritual, and cultural meaning that helps preserve local identity. Today, rapid social change, the spread of technology, and shifting priorities among younger generations have made the ritual less commonly practiced. This study explores ways to bring Pakon back into everyday life through community-based education and cultural documentation. Using a descriptive qualitative approach, data were gathered through participatory observation, in-depth interviews, and documentation. The findings show that revitalization works best when local communities take an active role. Educational programs within the community help pass down knowledge from older to younger generations, keeping the tradition alive in a natural way. At the same time, digital documentation creates lasting records, allowing the ritual to be preserved and shared more widely. When these two approaches come together, they do more than just protect the ritual. They also strengthen the sense of cultural identity, helping the Sasak community stay connected to its roots even as the world around them continues to change.